Does post acute care reduce the mortality of octogenarian and nonagenarian patients undergoing hip fracture surgery? - Yu-Wei Chiang; Yu-Jun Chang; Hui-Jen Huang; Cheng-Pu Hsieh; Yueh-Hsiu Lu (BMC Geriatrics, 2024)
Abstract Background With the increasing number of elderly individuals worldwide, a greater number of people aged 80 years and older sustain fragility fracture due to osteopenia and osteoporosis. Methods This retrospective study included 158 older adults, with a median age of 85 (range: 80–99) years, who sustained hip fragility fracture and who underwent surgery. The patients were divided into two groups, one including patients who joined the post-acute care (PAC) program after surgery and another comprising patients who did not. The mortality, complication, comorbidity, re-fracture, secondary fracture, and readmission rates and functional status (based on the Barthel index score, numerical rating scale score, and Harris Hip Scale score) between the two groups were compared. Results The patients who presented with fragility hip fracture and who joined the PAC rehabilitation program after the surgery had a lower rate of mortality, readmission rate, fracture (re-fracture and secondary fracture), and complications associated with fragility fracture, such as urinary tract infection, cerebrovascular accident, and pneumonia (acute coronary syndrome, out-of-hospital cardiac arrest, or in-hospital cardiac arrest. Conclusions PAC is associated with a lower rate of mortality and complications such as urinary tract infection, bed sore, and pneumonia in octogenarian and nonagenarian patients with hip fragility fracture.